2011
DOI: 10.1002/pon.2055
|View full text |Cite
|
Sign up to set email alerts
|

Work stress and well‐being in oncology settings: a multidisciplinary study of health care professionals

Abstract: The development and introduction of multilevel strategies to reduce demand, improve control and support perceptions are warranted, particularly for support staff.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
43
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 31 publications
3
43
0
6
Order By: Relevance
“…When comparing these finding with those of other international studies, a remarkably higher level of emotional exhaustion in medical oncologists was observed. The level of depersonalization in Flanders was also high, compared with the most other studies .…”
Section: Discussionmentioning
confidence: 51%
“…When comparing these finding with those of other international studies, a remarkably higher level of emotional exhaustion in medical oncologists was observed. The level of depersonalization in Flanders was also high, compared with the most other studies .…”
Section: Discussionmentioning
confidence: 51%
“…Although some research has demonstrated differences by gender and age, 13,17 other studies have found no impact of participant demographics. 30 The present study found no significant differences.…”
Section: Discussionmentioning
confidence: 94%
“…In fact, research suggests that understaffing and high patient load can result in low perceived degree of control and autonomy over decisions, 16 which can in turn decrease job satisfaction and increase the experience of burnout. 17 Research has also linked levels of burnout to patient satisfaction 18 and quality-of-care measures 19,20 such as frequency of urinary tract and surgical site infections among inpatients, even after controlling for staffing levels. 21 Stimpfel and colleagues 22 also found an association between length of nurses' shifts and burnout and patient dissatisfaction.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, research into the stressors and coping responses of ONs has often been undertaken as part of larger studies investigating burnout among cancer workers [1,2,5]. The most commonly cited stressors reported in a pilot study of Australian ONs included poor interprofessional communication and work overload [6], and the highest stress intensity levels were associated with making mistakes in patient care, feeling unable to complete required patient-care tasks within allotted time frames, and patient illness and death issues.…”
mentioning
confidence: 99%